Challenges in Access and Utilization of Sexual and Reproductive Health Services Among Youth During the COVID-19 Pandemic Lockdown in Uganda: An Online Cross-Sectional Survey - Mambo, Simon Binezero; Sikakulya, Franck Katembo; Ssebuufu, Robinson; Mulumba, Yusuf; Wasswa, Henry; Mbina, Solomon Adomi; Rusatira, Jean Christophe; Bhondoekhan, Fiona; Kamyuka, Louis K.; Akib, Surat Olabisi; Kirimuhuzya, Claude; Nakawesi, Jane; et al. (Frontiers in Reproductive Health, 2022)
Introduction Sexual and Reproductive Health access to Information services is still a pressing need for youth in Uganda even during the COVID-19 pandemic, which has disrupted health care access in many countries. The aim of this study was to explore the challenges in access and utilization of sexual and reproductive health services as faced by youth during the COVID-19 pandemic lockdown in Uganda. Methods This was a cross-sectional study carried out from 28th April 2020 to 11th May 2020 in Uganda. An online questionnaire was disseminated to youth aged between 18 and 30 years over a period of 14 days. The snowball sampling method was used to recruit participants. STATA version 14.2 was used for statistical analysis. Results Of 724 participants, 203 (28%) reported that they did not have access to information and/or education concerning sexual and reproductive health (SRH). More than a quarter of the participants (26.9%, n = 195) reported that testing and treatment services of sexually transmitted infections were not available during the lockdown, and 27.2% could not obtain contraceptive supplies. Access to HIV/AIDS care services and menstrual supplies was also impaired. Lack of transportation was the commonest factor cited as limiting access to SRH services during the lockdown (68.7%), followed by the long distance from home to SRH facilities (55.2%), high cost of services (42.2%) and the curfew (39.1%). Sexually transmitted infections were the commonest SRH problems related to SRH during the lockdown (40.4%) followed by unwanted pregnancy (32.4%) and sexual abuse (32.4%). Marital, educational, and employment status were significantly correlated with the reported experiences of the participants. Conclusion Access to SRH information and services for Ugandan youth was restricted during the COVID-19 lockdown and leaving them vulnerable to various SRH risks and adverse outcomes. Lack of transportation, long distances to health facilities, and high cost of services were important limiting factors. The Government and other stakeholders should incorporate SRH among the priority services to be preserved during future outbreaks.